Sitagliptin, a DPP-4 Inhibitor, Acutely Inhibits Intestinal Lipoprotein Particle Secretion in Healthy Humans - Xiao, Changting (American Diabetes Association, 2014)
The dipeptidyl peptidase-4 inhibitor sitagliptin, an antidiabetic agent, which lowers blood glucose levels, also reduces postprandial lipid excursion after a mixed meal. The underlying mechanism of this effect, however, is not clear. This study examined the production and clearance of triglyceride-rich lipoprotein particles from the liver and intestine in healthy volunteers in response to a single oral dose of sitagliptin. Using stable isotope tracer techniques and with control of pancreatic hormone levels, the kinetics of lipoprotein particles of intestinal and hepatic origin were measured. Compared with placebo, sitagliptin decreased intestinal lipoprotein concentration by inhibiting particle production, independent of changes in pancreatic hormones, and circulating levels of glucose and free fatty acids. Fractional clearance of particles of both intestinal and hepatic origin, and production of particles of hepatic origin, were not affected. This pleiotropic effect of sitagliptin may explain the reduction in postprandial lipemia seen in clinical trials of this agent and may provide metabolic benefits beyond lowering of glucose levels.